PSYCHOLOGICAL METHODS OF MANAGING A PHYSICAL EDUCATION TEACHER'S ACTIVITIES - Ergashaliyeva Shirinxon Soyibjon qizi (Bright Mind Publishing, 2025)
The role of psychological methods in managing the activities of a physical education teacher. Teaching the effective use of psychological methods in teaching physical education lessons to preschool, school, and vocational college teachers, sports coaches, educators, and mentors.
Keywords: Intelligence, endurance, sports sections, track and field, football, volleyball, basketball.